Coaching wrestling successfully - Gable, Dan (Human Kinetics, 1999)
In Coaching Wrestling Successfully, Gable shares the special philosophy, motivational techniques, training plans, teaching methods, match strategies, and evaluation systems he used to build his wrestling dynasty. Gable also provides a rare insight into the influential people, lasting lessons, inner drive, and mental focus that spurred him to championship after championship. If you coach wrestlers, this book is a blueprint on how to be the best. If you wrestle, this book challenges you to develop yourself into a tough, competitive champion. And if you're a wrestling fan, this book is an inside look at the greatest figure ever in the sport.